The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s0100-879x2005000800016
|View full text |Cite
|
Sign up to set email alerts
|

The biological effects of high-pressure gas on the yeast transcriptome

Abstract: The aim of the present study was to examine the feasibility of DNA microarray technology in an attempt to construct an evaluation system for determining gas toxicity using high-pressure conditions, as it is well known that pressure increases the concentration of a gas. As a first step, we used yeast (Saccharomyces cerevisiae) as the indicator organism and analyzed the mRNA expression profiles after exposure of yeast cells to nitrogen gas. Nitrogen gas was selected as a negative control since this gas has low t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Expression studies have shown that YLR162W transcript level was increased by 4.3 folds in cells over-expressing MLH1 [4] i.e., under conditions of elevated spontaneous mutation rate and genomic instability. YLR162W expression was also significantly elevated during high-pressure stress [5], upon Mg 2? starvation [6], during response to a-factor (50 folds) [7] and in stationary phase [8].…”
Section: Introductionmentioning
confidence: 94%
“…Expression studies have shown that YLR162W transcript level was increased by 4.3 folds in cells over-expressing MLH1 [4] i.e., under conditions of elevated spontaneous mutation rate and genomic instability. YLR162W expression was also significantly elevated during high-pressure stress [5], upon Mg 2? starvation [6], during response to a-factor (50 folds) [7] and in stationary phase [8].…”
Section: Introductionmentioning
confidence: 94%